SISTEM INFORMASI PENDIDIKAN PADA PENERIMAAN SISWA SEKOLAH MASTER (MASJID TERMINAL DI KOTA DEPOK JAWA BARAT - Lasminiasih; Rooswhan Budhi Utomo; Guntur Eka Saputra; Elbi Wiseno (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
School is a place to study and build character in children from an early age toteenagers to solve problems. The purpose of this study was to determine theadministrative system for the registration of new students at the TermilalMosque (MASTER) school in Depok. The research method used is a qualitativedescriptive method. The technique of collecting data was by conducting directobservations and interviews with the founders and administrative staff of theMASTER Terminal MASTER Mosque School Foundation in Depok. The resultsof this study are Master schools consist of several educational levels includingEarly Childhood Education (PAUD), Elementary School (SD), Junior HighSchool (SMP), and High School (SMA). The registration system at Master'sschools is still carried out offline (outside the network), namely by comingdirectly to the school from registration to announcement of the results of theselection of new students. The system implemented, although still using theoffline system, is in accordance with the educational administration standardsset by the government.